2017
DOI: 10.2147/dddt.s87251
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of essential oil composition of Iranian and Indian <em>Nigella sativa</em> L. extracted using supercritical fluid extraction and solvent extraction

Abstract: The objective of this study was to compare the oil extraction yield and essential oil composition of Indian and Iranian Nigella sativa L. extracted by using Supercritical Fluid Extraction (SFE) and solvent extraction methods. In this study, a gas chromatography equipped with a mass spectrophotometer detector was employed for qualitative analysis of the essential oil composition of Indian and Iranian N. sativa L. The results indicated that the main fatty acid composition identified in the essential oils extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 21 publications
(26 reference statements)
3
21
0
Order By: Relevance
“…The results of the present study showed that NSO is an important source of bioactive compounds, especially p-cymene, TQ and α-thujene. The percentages of the identified compound are consistent with other reported results [ 30 , 31 ].…”
Section: Discussionsupporting
confidence: 93%
“…The results of the present study showed that NSO is an important source of bioactive compounds, especially p-cymene, TQ and α-thujene. The percentages of the identified compound are consistent with other reported results [ 30 , 31 ].…”
Section: Discussionsupporting
confidence: 93%
“…The N. sativa seed contain 26-34% fixed oil of which the major fatty acids are linoleic acid (64.6%) and palmitic acid (20.4%). The seed oil is comprised of 0.4%–2.5% essential oil [9, 10]. Amongst different active constituents reported so far, thymoquinone found as major component of the essential oil is the most bioactive compound and exhibits wide ranging therapeutic benefits [11].…”
Section: Introductionmentioning
confidence: 99%
“…The composition of terpenes, characteristic of such an essential oil, does not correspond to the qualitative composition (and quantitative content) of terpenes, which have been converted to fatty oil in the process of its production by pressing. In the extraction of fatty oil, a large part of the terpenes are extracted together with triacylglycerides, but their composition and content also significantly vary and very much depends on the properties of the extractant used [37]. In turn, the variability of the content of essential oil in the seeds indicates the unreliability and unacceptability of the indicator "content of essential oil" for the purpose of standardization of black cumin.…”
Section: Advances In Engineering Research Volume 151mentioning
confidence: 99%